PENGARUH WAKTU FERMENTASI SERTA DOSIS EM-4, MOLASE TERHADAP SIFAT FISIK DAN KIMIA BIOURINE KELINCI - Nuruddin, Muhammad; Nopriani, Lenny Sri (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Rabbits are animals that have the potential to be cultivated, but the liquid waste they produce can cause pungent odors. The solution is to process the waste into biourine. This study aims to determine the effect of fermentation time and dosages of EM-4 and molasses on the physical and chemical properties of rabbit biourine, and to determine the best treatment. This research was conducted from March to May 2025 in Pandanrejo Village, Bumiaji District, Batu City. This study used a factorial completely randomized design with 2 factors with 3 replications. The treatment consisted of a combination of fermentation time (0, 14, and 28 days) and dosages of EM-4 (0, 20, 40 and 60 mL) and molasses (0, 25, 50 and 75 mL). The results showed that the treatments had a significant effect on color, odor, pH and N-total levels, but no significant effect on phosphorus (P2O5) and potassium (K2O) levels. The best treatment was obtained in the W2D3 treatment, which produced biourine with a dark brown color, a distinctive fermentation odor, pH 4.57, N-total content of 0.158%, phosphorus (P2O5) 0.024% and potassium (K2O) 0.381%.